Using a bespoke situated digital kiosk to encourage user participation in healthcare environment design. - Mackrill, J.; Marshall, P.; Payne, S.R.; Dimitrokali, E.; Cain, R. (Applied Ergonomics)
Involving users through participation in healthcare service and environment design is growing. Existing approaches and toolkits for practitioners and researchers are often paper based involving workshops and other more traditional design approaches such as paper prototyping. The advent of digital technology provides the opportunity to explore new platforms for user participation. This paper presents results from three studies that used a bespoke situated user participation digital kiosk, engaging 33 users in investigating healthcare environment design. The studies, from primary and secondary care settings, allowed participant feedback on each environment and proved a novel, engaging "21st century" way to participate in the appraisal of the design process. The results point toward this as an exciting and growing area of research in developing not just a new method of user participation but also the technology that supports it. Limitations were noted in terms of data validity and engagement with the device. To guide the development of user participation using similar situated digital devices, key lessons and reflections are presented.